Respuesta :

(5,-8)
thats what i got

Substitution involves finding the value of one variable by isolating the variable, and then plugging this value in to the other equation. For example, I will isolate y on x + y = -3. x + y = -3 ----> x + y - x = -3 - x ---> y = -x - 3. Now that you have that, plug it in to the other equation (5x + 2y = 9). 5x + 2y = 9 ----> 5x + 2(-x - 3) = 9 ---> 5x -2x - 6 = 9. Now, solve for x. 5x -2x - 6 = 9. ---> 3x - 6 = 9. ---> 3x - 6 + 6 = 9 + 6 ---> 3x = 15 ---> 3x / 3 = 15 / 3 ---> x = 5. Now that you have the numerical value of x, plug it in to the equation we manipulated for (y = -x - 3). y = -x - 3 ---> y = -(5) - 3 ---> y = -8. And that gives us (5, -8). Now that you've done that, test the values in one of the original equations. 5x+2y=9 --> 5(5) + 2(-8) ?= 9 --> 25 - 16 = 9. The statement is true, so the answer is valid.